2022
DOI: 10.22541/au.165827703.34856696/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential patterns of fish sensitization in Asian populations: implication for precision diagnosis

Abstract: Background The current diagnostics of fish allergy lack sufficient accuracy such that more reliable tests such as component-resolved diagnosis (CRD) are urgently needed. This study aimed at identifying fish allergens of salmon and grass carp and evaluating the sensitization pattern towards the identified allergens in fish allergic subjects from two distinct populations in Asia. Methods One hundred and three fish allergic subjects were recruited from Hong Kong (67 subjects) and Japan (46 subjects). Western blot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(40 reference statements)
0
1
0
1
Order By: Relevance
“…Parvalbumin is a major allergen that is found in fish muscle; however, its levels vary considerably among fish species. A study comprising 103 participants with fish allergies, collectively, from Hong Kong and Japan analyzed sensitization profiles of fish allergens [45 ▪ ]. The study revealed that fish allergen sensitization profiles varied between populations, but β-parvalbumin and collagen were important biomarkers for fish allergy in the Asian population.…”
Section: Allergens Related To Diagnosing Food Allergymentioning
confidence: 99%
“…Parvalbumin is a major allergen that is found in fish muscle; however, its levels vary considerably among fish species. A study comprising 103 participants with fish allergies, collectively, from Hong Kong and Japan analyzed sensitization profiles of fish allergens [45 ▪ ]. The study revealed that fish allergen sensitization profiles varied between populations, but β-parvalbumin and collagen were important biomarkers for fish allergy in the Asian population.…”
Section: Allergens Related To Diagnosing Food Allergymentioning
confidence: 99%
“…Hasil pengamatan gambaran darah terdeteksi dibawah standar (abnormal). Diagnosis merupakan suatu kegiatan yang dilakukan untuk mengenal suatu jenis penyakit sebagai langkah awal untuk penanggulangan penyakit ikan (Wai et al, 2023). Wilayah budidaya perikanan di daerah Cibeureum memiliki kondisi geografis dengan sumberdaya perairan yang luas, maka dari itu banyak para pembudidaya yang memanfaatkan kondisi lingkungan sekitar dengan membudidayakan ikan di daerah tersebut.…”
Section: Hasil Dan Pembahasanunclassified